An Efficient Approach To Voltage Stability Evaluation Using Tellegen’s Equations - Payman Mohammadi; Hamid Lesani (Institute of Advanced Engineering and Science, 2013)
In this paper, the adjoint networks based on Tellegen’s Theorem are used to improve the PV curve assessment. PV curve is the most widely accepted method for determining the margin of the power system state to the voltage collapse point. The repetitive power flow and continuation power flow are used to access PV curves through tracing the power flow solutions for the change of loads. Since the Minimum Jacobi matrix eigenvalue is practically close to zero at neighbor voltage collapse point, there is a restriction in order to access the voltage stability level by repetitive power flow method. This problem solved by appropriate combination of adjoint networks based on Tellegen’s Theorem and conventional equations. The proposed method was tested on SWCC test system. Comparison of three method results show advantages and efficiency of the proposed method.DOI:http://dx.doi.org/10.11591/ijece.v3i2.1964